Mosby's physical examination DVD series : DVD 14, Neurologic system [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 17 minute video shows the steps needed to perform three essential parts of the neurologic examination: assessment of the patient's motor function, sensory function, and reflexes. (The two other parts of a complete neurologic examination are covered in the Neurologic System: Mental Status and Cranial Nerves video.) With the patient in various positions, this video demonstrates how to evaluate coordination, fine motor skills, and balance; primary and cortical sensory functions; and superficial and deep tendon reflexes, using the appropriate equipment. The video shows expected findings in healthy adults and presents modifications of assessment techniques and variations in expected findings for pediatric and geriatric patients."Publisher's website